Nonverbal Signs in the Qur’an: Integrating Theology, Semiotics, and Communication Studies - Alif Hibatullah; Husein Aziz (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This study explores the concept of sign language in the Qur’an as a universal form of communication rooted in human nature. Unlike previous studies focusing on verbal ethics in Islamic communication, this research highlights nonverbal expressions silence, gestures, and visual signs as legitimate and sacred forms of al-bayān (articulation of meaning). Through a qualitative-descriptive library research approach, the study employs thematic Qur’anic exegesis (tafsīr mauḍū‘ī), nonverbal communication theory as articulated by Ray L. Birdwhistell, and theological semiotics to analyze verses depicting prophetic gestures: prophet Zakariyya’s symbolic silence Surah Āli ʿImran verse 41; Surah Maryam verse 10, Maryam’s gesture toward prophet ‘Isa surah Maryam verse 26, prophet Musa’s radiant hand Surah Ṭaha verse 22, and the regulation of voice and conduct in communication Surah al-Ḥujurat verses 2–3. Findings reveal that nonverbal communication in the Qur’an functions not merely as an alternative to speech but as a divinely sanctioned medium of spiritual awareness and worship. Silence becomes a means of purification and surrender, gestures become extensions of divine will, and light serves as a visual symbol of divine truth. Theologically, this study affirms that al-bayān represents a holistic system of meaning (niẓām al-maʿnā), integrating verbal, paralinguistic, and nonverbal dimensions into a unified Qur’anic communication paradigm. The research contributes to Qur’anic communication studies by proposing a tauḥīdī framework in which silence, movement, and light operate as sacred languages of devotion and consciousness demonstrating that divine communication transcends speech and resonates within all dimensions of human expression.